The issues on the use of Islamic attributes in food products labelling and marketing in Malaysia - Osman, Suraiya; Jalil, Abdullaah; Ab. Rahman, Suhaimi (2019)
The aim of this study is to discover the types of use of Islamic attributes in food products’ labelling and to investigate the extent to which the use of Islamic attributes impacts the consumer and the Islamic dignity. Library research was carried out to collect relevant information and data. The materials not only limited to the English language but also cover Malay language materials. The keywords searches are ‘Prophetic Food,’ ‘Sunnah food,’ ‘Ruqyah,’ and ‘misuse of religion.’ There are various types of misuse, which is first Quranrelated such as Ruqyah, secondly Sunnah-related such as using the term Prophetic foods or the word Sunnah itself, thirdly by using Islamic icons. Fourthly, by using Islamic performance of worships such as prostration in prayers and the fifth category is using an Islamic or Muslim’s name. The last category is by using Jawi writings or Arabic terms in the label or trademark. These misapplications may lead to numerous effects, among others degrading the authority of Sunnah, health concern and exploiting Islam for commercial gain. These findings may act as a starting point in proposing some guidelines to the policymakers on the use of Islamic attributes in food product labeling and marketing in Malaysia. This study uncovers various types of misuse of Islamic attributes in food products’ labeling and marketing. It will be an eye-opener to the consumer on the marketing trait and the policymaker to provide the appropriate guidelines to it